CLIL experiences in secondary and tertiary education In search of good practices - Doiz, Aintzane; Doiz, Aintzane; Lasagabaster, David (Peter Lang, 2016)
This volume clearly documenting research into CLIL and EMI settings is welcome and timely. A range of researchers rise to the challenge of providing deeper understanding and interpretations of key issues in ways which enable readers to adapt the approaches and ideas to inform their own practices. The nature of integration underpins each chapter and each study in creative, relevant ways at different levels. Bringing together educationalists, linguists and subject specialists provides a shared context for surfacing deeply held beliefs and providing clearer pathways for closer understanding and adaptations to define, refine and support integrated learning. Moreover, integrating theoretical perspectives and research methods is also a feature of the volume which not only informs classroom practices but also goes further into the motivations which operationalize and underpin current drives towards internationalization in universities. The studies in each of the eight chapters in the volume are usefully built on an in-depth critical review of research in the field which enables the reader to carefully position the research and the challenging questions posed. (Do Coyle, University of Aberdeen)